Podere Riosto: A “Forchetta” in the Road - Michael Braun; Bambi Douma (Wine Business Journal, 2016)
Alessandro and Alessandra Galletti were the owners of a small family-owned and operated vineyard in Northern Italy. They had owned Podere Riosto for 20 years and had grown the business to EUR 1million in annual sales. Their flagship product, Pignoletto, was a highly regarded and award-winning wine. Recently, however, Alessandro faced challenges relating to both business and family. He was unsure whether to invest in his wine business or follow a new opportunity in tourism; he was also considering expanding sales on a more global scale but knew there were many risks involved. All the while, he was confronted with a succession dilemma, as his son was not engaged in the business and his daughter wanted to manage it all.